Evaluating the Functional Properties of Spray-Dried Porcine Plasma in Gilthead Seabream (Sparus Aurata) Fed Low Fish Meal Diets - Reyes-Lopez, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Blood by-products are an untapped source of high-quality ingredients for aquafeeds, containing a broad variety of cytokines, hormones, growth factors, proteins, bioactive peptides, and amino acids. The effects of the spray-dried porcine plasma (SDPP), a type of processed animal protein on several immune parameters, were evaluated in sea bream using ex vivo and in vitro assays. In this study, fish were fed with two isoproteic, isolipidic, and isoenergetic diets: control diet (7% fish meal, FM) and SDPP diet (2% FM and 5% SDPP). At the end of the 92-days trial, those fed the SDPP diet were larger in body weight (p < 0.05) without differences in feed conversion ratio (p > 0.05). The ex vivo immune stimulation of splenocytes indicated that SDPP had a beneficial effect in promoting systemic immunity, since the surface cell marker (cd4), pro- (il-1β), and anti-inflammatory (tgf-β1) cytokines, and genes involved in humoral immunity (IgM) were up-regulated. The co-culture assays of skin mucus corroborated that SDPP enhanced the antibacterial capacity of mucus against V. anguillarum. In addition, main mucus biomarkers did not show significant differences, except for cortisol levels which were lower in the SDPP diet. The present study indicated that SDPP may be considered a functional ingredient in aquafeeds formulated with low FM levels. © 2022 by the authors.